STUDIES ON FOLLICULAR DEVELOPMENT AND OVARIAN STEROID PROFILE IN SEASONAL ANESTRUS GOATS
The present study was conducted with the objective to study the follicular growth and steroid profile in acyclic goats. The seasonal anestrus goats (n=7